Planting Portals during the Apocalypse : Modelling Collaborative Futures through Folklore and Ground Responsiveness in a Climate-Endangered North - Galadriel González Romero 1992- (2024)
This thesis explores a multi-being interdependent future as a model for a sustainable coexistence post-climate apocalypse. Research into folklore as a way in which humans interact with their environment, with a focus on Icelandic and Norse apocalypse-related stories, is combined with research into climate change and arctic amplification. The findings juxtapose the prophecy-poem Völuspá and our current climate catastrophe. Science and folklore are ways in which humans try to understand the world, the combination of which results in the proposed genre science-folklore as a field that re-entangles art and science. Within artistic research, I develop techniques such as using intuition and forces of nature as signs to be able to collaborate with non-human beings. A real-life application of these approaches is ground responsiveness, a site-specific art-making method that exemplifies the interconnected existence. The physical manifestation of this thesis is the exhibition series A Portal to the End of the World where, in collaboration with soil, humans from different fields of knowledge, hidden people, and a seed, we create a portal at the Akureyri Botanical Garden to announce the apocalypse and serve as an interbeing gathering point to bring attention to our global climate apocalypse.